Pengaruh Kepatuhan Wajib Pajak dan Pemahaman Sanksi Pajak Terhadap Penggelapan Pajak di Samarinda - Desi Cindy Preniaty Limbong; Valentine Siagian; Judith Tagal Gallena Sinaga (Universitas 17 Agustus 1945 Semarang, 2024)
The aim of this research is to determine the effect of taxpayer compliance and understanding of tax sanctions on tax evasion. This research was conducted using a qualitative approach by distributing questionnaires. The target respondents in filling out the questionnaire were individual taxpayers in Samarinda, the number of respondents was 51 people. The data obtained was then tested with descriptive statistics, multiple linear analysis, classical assumption analysis, hypothesis testing and coefficient of determination. The results of this research show negative and significant results on taxpayer compliance with tax evasion and a negative but not significant influence on understanding tax sanctions for tax evasion. More exposure is needed so that taxpayers better understand tax sanctions.